Taarud Al-Adillah Dalam Mukhtalif Al-Hadis Menurut Muhammad Hashim Kamali - Umar, Subehan Khalik; Mujaddid (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2022)
This study describes the thoughts of the Afghan-born Muhammad Hashim Kamali about mukhtalif al-hadith. The purpose of this study is to reveal in depth the thoughts of Kamali and to elaborate the study of mukhtalif al-hadith while comparing it with the thoughts of other scholars. Literature study became the main method of this research and resulted in the finding that Kamali's theory of mukhtalif al-hadith was colored by his educational background as a law graduate. Kamali traces the direct intersection between the theory of the study of the settlement of the arguments that intersect in the study of hadith by using the theoretical approach of ushul fiqh. Of course, these findings reveal that there is a close relationship between the study of ushul and the study of hadith.